How to Maximize Children's Involvement in Non-therapeutic Research—Lessons Learnt From EFFECTOR - Van De Maele, Karolien; Devlieger, Roland; Gies, Inge (Frontiers in Pediatrics, 2020)
Background: Children are vulnerable study subjects, especially in non-therapeutic research. Nowadays more attention is paid to the children's voice in both decision-making on participation and their experience of clinical research procedures. Methods: We share our experiences from a long-term, cross-sectional, non-therapeutic follow-up study in the offspring of mothers who participated in scientific research during their pregnancy. Results: During the data collection process, different strategies were developed to achieve a satisfactory participation rate with a focus on the involvement of the children. All study documents and measurements were assembled into a superhero framework. This theme is flexible and attracts children of a wide age-span. In order to inform the children before the study visit, a visually attractive assent was created as well as a superhero video. During the study visit, a sticker diploma was used with similar visuals from the assent. The toddlers received a superhero-cape. The children were involved in the decision-making process during the whole process. Discussion and conclusion: From our experience during the EFFECTOR data collection process, parents and their children can be motivated to participate in a long-term, non-therapeutic, follow-up study when child friendly and adequate communication is used. Framing in a superhero theme is simple and suitable for children of a wide age-span.